2023
DOI: 10.1049/cds2.12158
|View full text |Cite
|
Sign up to set email alerts
|

500 V breakdown voltage in β‐Ga2O3 laterally diffused metal‐oxide‐semiconductor field‐effect transistor with 108 MW/cm2 power figure of merit

Abstract: The authors’ present a silicon‐on‐insulator (SOI) laterally diffused metal‐oxide‐semiconductor field‐effect transistor (LDMOSFET) with β‐Ga2O3 , which is a large bandgap semiconductor (β‐LDMOSFET), for increasing breakdown voltage (VBR) and power figure of merit. The fundamental purpose is to use a β‐Ga2O3 semiconductor instead of silicon material due to its large breakdown field. The characteristics of β‐LDMOSFET are analysed to those of standard LDMOSFET, such as VBR, ON‐resistance (RON), power figure of mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The basic physical properties and figures of merit (FOM) of commonly used semiconductor materials are shown in Table 1. For this reason, researchers have obtained plenty of results related to β-Ga 2 O 3 -based FETs [12][13][14], SBDs [15][16][17][18], and solarblind ultraviolet photodetectors [19][20][21]. In 2023, Wang et al [13] demonstrated a metalheterojunction composite field-effect transistor that exhibited a breakdown voltage (BV) of around 2160 V. In addition, the corresponding R ON,SP was 6.35 mΩ•cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The basic physical properties and figures of merit (FOM) of commonly used semiconductor materials are shown in Table 1. For this reason, researchers have obtained plenty of results related to β-Ga 2 O 3 -based FETs [12][13][14], SBDs [15][16][17][18], and solarblind ultraviolet photodetectors [19][20][21]. In 2023, Wang et al [13] demonstrated a metalheterojunction composite field-effect transistor that exhibited a breakdown voltage (BV) of around 2160 V. In addition, the corresponding R ON,SP was 6.35 mΩ•cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are also many research works about novel structures, including surrounded stress dielectric layer LDMOS [2], folded accumulation LDMOS [5], optimized high-temperature oxide field plate, and the decoupled plasma nitridation LDMOS [6], H-shape shallow-trench isolation (STI) field plate LDMOS [7], or even silicon-on-insulator LDMOS [8], and high breakdown voltage devices with new material Ga 2 O 3 [9]. These papers provided certain innovative device structures with encouraged R on,sp or BV ds,max performance by simulation results or small amounts of electrical results.…”
Section: Introductionmentioning
confidence: 99%